Classification and coding: Approach of different international organizations - Hunt, Ülo; Koppel, Ott (Transport, 2006)
Transportation plays a significant role in the world. This paper deals with harmonization of classification and coding systems, which is of fundamental importance in everyday freight handling practice. First Published Online: 27 Oct 2010